Specifics of formal and legal issues in processes of revitalizing post-industrial buildings = Specyfika zagadnień formalno-prawnych w procesach rewitalizacji obiektów poprzemysłowych - Kochański, Paweł (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article deals with issues from the initial phase of the investment process connected with revitalizing postindustrial buildings: planning and programming investments in the functional and financial scope, as well as designing. The described formal and legal aspects are the result of a study of a few projects concerning the adaptation of buildings to serving a new function in Zielona Góra and Żagań.
Keywords: revitalisation; post-industrial buildings; investment planning; legal issues; rewitalizacja; obiekty poprzemysłowe; planowanie inwestycji; programowanie inwestycji; zagadnienia prawne